Conjugated linoleic acid influences the metabolism of tocopherol in lactating rats but has little effect on tissue tocopherol concentrations in pups. Issue 1 (December 2016) - Zeitz, Johanna; Most, Erika; Eder, Klaus
Abstract Background Conjugated linoleic acid (CLA) is known to affect the lipid metabolism in growing and lactating animals. However, potential effects on the metabolism of fat-soluble vitamins in lactating animals and co-occurring effects on their offspring are unknown. We aimed to investigate the effects of dietary CLA on concentrations of tocopherol in various tissues of lactating rats and their offspring and expression of genes involved in tocopherol metabolism. Methods Twenty-eight Wistar Han rats were allocated to 2 groups and fed either a control diet (control group) or a diet containing 0.9 % of cis-9, trans-11 and trans-10, cis-12 (1:1) CLA (CLA group) during pregnancy and lactation. Feed intake of dams and body weight of dams and their pups were recorded weekly. Tocopherol concentrations in various body tissues were determined at day 14 of lactation in dams and 1, 7 and 14 days after birth in pups. Expression of selected genes involved in metabolism of tocopherol was determined in dams and pups. The data were statistically analysed by analysis of variance. Results Feed intake and body weight development of nursing rats and their pups was similar in both groups. In livers of CLA-fed dams, tocopherol concentrations decreased by 24 % but expression of TTPA and CYP3A1, involved in tocopherol transport and metabolism, were not influenced. In the dams' adipose tissue, gene expression of receptors involved in tissue tocopherol uptake, LDLR and SCARB1, but not of LPL, increased by 30 to 50 % and tocopherol concentrations increased by 47 % in CLA-fed compared to control dams. Expression of LPL, LDLR and SCARB1 in mammary gland was not influenced by CLA-feeding. Tocopherol concentrations in the pup's livers and lungs were similar in both groups, but at 14 days of age, adipose tissue tocopherol concentrations, and LDLR and SCARB1 expression, were higher in the CLA-exposed pups. Conclusions We show that dietary CLA affects tissue concentrations of tocopherol in lactating rats and tocopherol metabolism in rats and pups, but hardly influences tissue tocopherol concentrations in their offspring. This indicates that supplementation of CLA in pregnant and lactating animals is uncritical considering the tocopherol status of new-borns.